Di-n-butyl{4-hydroxy-N0-[(2-oxido-1-naphthyl-jO) methylene]benzohydrazidato-j2 O,N0}tin(IV) - Md. Abu, Affan; Norrihan, Sam; Fasihuddin Badruddin, Ahmad; Seik Weng, N (International Union of Crystallography, 2010)
The deprotonated Schiff base ligand in the title compound, [Sn(C4H9)2(C18H12N2O3)], O,N,O'-chelates to the Sn atom, which is five-coordinated in a cis-C2NO2Sn trigonal-bipyramidal environment. The apical sites are occupied by the O atoms [O-Sn-O = 155.2 (2)°]. The hydroxy group is a hydrogen-bond donor to the two-coordinate N atom of an adjacent molecule, the hydrogen-bonding interaction giving rise to a helical chain running along the c axis. The carbon atoms of the butyl chains are equally disordered over two positions.